CARs derived from broadly neutralizing, human monoclonal antibodies identified by single B cell sorting target hepatitis B virus-positive cells - Schreiber, Sophia; Dressler, Lisa S.; Loffredo-Verde, Eva; Asen, Theresa; Färber, Stephanie; Wang, Wenshi; Groll, Tanja; Chakraborty, Anindita; Kolbe, Fenna; Kreer, Christoph; Kosinska, Anna D.; Simon, Sylvain; et al. (Frontiers in Immunology, 2024)
To design new CARs targeting hepatitis B virus (HBV), we isolated human monoclonal antibodies recognizing the HBV envelope proteins from single B cells of a patient with a resolved infection. HBV-specific memory B cells were isolated by incubating peripheral blood mononuclear cells with biotinylated hepatitis B surface antigen (HBsAg), followed by single-cell flow cytometry-based sorting of live, CD19 + IgG + HBsAg + cells. Amplification and sequencing of immunoglobulin genes from single memory B cells identified variable heavy and light chain sequences. Corresponding immunoglobulin chains were cloned into IgG1 expression vectors and expressed in mammalian cells. Two antibodies named 4D06 and 4D08 were found to be highly specific for HBsAg, recognized a conformational and a linear epitope, respectively, and showed broad reactivity and neutralization capacity and reactivity against all major HBV genotypes. 4D06 and 4D08 variable chain fragments were cloned into a 2 nd generation CAR format with CD28 and CD3zeta intracellular signaling domains. Interestingly, ourThe new CAR constructs displayed a higher functional avidity despite lower expression levels when expressed on primary human T cells. than a previously generated CAR recognizing the HBV envelope proteins. All CAR-T cells CAR-grafted T cells proved to be polyfunctional regarding cytokine secretion and killed HBV-positive target cells with similar efficacy. Interestingly, background activation of the 4D08-CAR recognizing a linear instead of a conformational epitope was consistently low the lowest. In a preclinical model of chronic HBV infection, murine T cells grafted with the 4D06 and the 4D08 CAR showed on target activity indicated by a transient increase in serum transaminases, and a lower number of HBV-positive hepatocytes in the mice treated. This study demonstrates an efficient and fast approach to identifying pathogen-specific monoclonal human antibodies from small donor cell numbers for the subsequent CAR generation of new CARs.